2010
DOI: 10.1002/jssc.200900597
|View full text |Cite
|
Sign up to set email alerts
|

Development, validation, and implementation of capillary gel electrophoresis as a replacement for SDS‐PAGE for purity analysis of IgG2 mAbs

Abstract: Capillary gel electrophoresis (CGE) methods with UV detection were developed for reduced and non-reduced mAb analysis. These methods can be used to evaluate mAb purity, offering more reproducible quantitation compared with that of traditional SDS-PAGE methods. These CGE methods have been utilized as platform technology for bioprocess development, formulation development, mAb characterization, drug substance/drug product release testing as well as a required methodology for stability testing. We have found thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 25 publications
(44 reference statements)
2
48
0
1
Order By: Relevance
“…The disulfide bonds which are responsible for the tetrameric structure of monoclonal antibodies are disrupted (reducing) or protected (non-reducing) during heat denaturation by reducing or alkylating reagents respectively [15,16]. In the non-reducing condition, sensitivity of antibodies to partial reduction and fragmentation necessitate molecule dependent optimization of sample preparation [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The disulfide bonds which are responsible for the tetrameric structure of monoclonal antibodies are disrupted (reducing) or protected (non-reducing) during heat denaturation by reducing or alkylating reagents respectively [15,16]. In the non-reducing condition, sensitivity of antibodies to partial reduction and fragmentation necessitate molecule dependent optimization of sample preparation [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, peak tailing was observed when new‐coated capillaries were used, which has been interpreted to result from protein adsorption to the capillary surface . This phenomenon occurred in two of three newly installed capillaries, which might be an indication of the variability in capillary polyacrylamide‐based surface coating between batches.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al [48] optimized a similar method to analyze mAb1 drug substance under both reduced and non-reduced conditions. Lancher et al [127] established a generic method for monitoring disulfide isomer heterogeneity in IgG2 antibodies, and applied this method for purity analysis of reduced and non-reduced IgG2 mAbs [128]. Rustandi et al [129] reported a wide range of applications of CGE for mAb product development, including purity analyses for product release, product-related impurities during process and cell-culture development, and product stability evaluation.…”
Section: Applicationsmentioning
confidence: 99%